1961
DOI: 10.1139/z61-020
|View full text |Cite
|
Sign up to set email alerts
|

The in Vitro Hatching of Ascaris Lumbricoides Eggs

Abstract: The stimulus leading to in vitro hatching of Ascaris lumbricoides eggs consisted of four components as follows: (1) a temperature similar to that of homoiothermic animals, (2) pCO2 approximating 5 vol.%, (3) pH near 7.0, (4) non-specific reducing conditions such as are established by cysteine, glutathione, sodium hydrosulphite, sodium bisulphite, or sulphur dioxide. Application of this stimulus resulted in 80–95% hatching in 3 hours, the observed morphological changes corresponding to those occurring during in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

1974
1974
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(32 citation statements)
references
References 4 publications
1
30
0
1
Order By: Relevance
“…Rogers (1958) observed hatching following the addition of both carbon dioxide and reducing agents to an in vitro culture of A. lumbricoides eggs. A similar result was reported by Fairbairn (1961), who demonstrated in vitro hatching of A. lumbricoides eggs after the addition of sulfur dioxide, sodium chloride, and sodium bicarbonate to an atmosphere of 5% carbon dioxide and 95% nitrogen. Jaskoski and Colucci (1964) tested the eect of ox bile on egg hatching and found that hatching in the presence of 90% bile failed to produce viable larvae, regardless of carbon dioxide supplementation, whereas a 10% bile concentration resulted in low hatching percentages (25±50%).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Rogers (1958) observed hatching following the addition of both carbon dioxide and reducing agents to an in vitro culture of A. lumbricoides eggs. A similar result was reported by Fairbairn (1961), who demonstrated in vitro hatching of A. lumbricoides eggs after the addition of sulfur dioxide, sodium chloride, and sodium bicarbonate to an atmosphere of 5% carbon dioxide and 95% nitrogen. Jaskoski and Colucci (1964) tested the eect of ox bile on egg hatching and found that hatching in the presence of 90% bile failed to produce viable larvae, regardless of carbon dioxide supplementation, whereas a 10% bile concentration resulted in low hatching percentages (25±50%).…”
Section: Discussionsupporting
confidence: 87%
“…Hatching of A. lumbricoides eggs in vitro has been achieved in an atmosphere of carbon dioxide and reducing agents (Rogers 1958) or using sulfur dioxide, sodium chloride, and sodium bicarbonate in an atmosphere of 5% carbon dioxide and 95% nitrogen (Fairbairn 1961). In other studies, A. suum eggs have been hatched using high carbon dioxide concentrations without reducing agents (Jaskoski and Colucci 1964), carbon dioxide combined with glass beads and magnetic stirring (Stromberg and Soulsby 1976), or glass beads with magnetic stirring in the absence of carbon dioxide (Urban et al 1981).…”
Section: Introductionmentioning
confidence: 99%
“…The worms were collected in a beaker containing 50 ml of normal saline (0.9%), and transported to the Helminthology Laboratory of the Department of Veterinary Parasitology and Entomology, Ahmadu Bello University, Zaria. The uteri of the worms were dissected open using forceps into a petri dish and washed with 0.5 M KOH solution into a beaker as previously described (Fairbairn, 1961). The eggs were then agitated gently in the KOH solution for 30 minutes in order to dissolve the sticky albuminous layer.…”
Section: Isolation Of Infective Eggsmentioning
confidence: 99%
“…The suspension was then transferred into centrifuge tubes and spun at 349 relative centrifugal force (rcf) xg for 3 minutes, and the supernatant gently decanted, leaving about 0.5 ml which contained the eggs. The eggs were then washed two times with distilled water and twice more with embryonating fluid (0.1 M sulphuric acid) according to the method described by Fairbairn (1961). The eggs collected were suspended in fresh embryonating fluid, transferred to Petri dishes and incubated for 30 days at 27˚C (Dubinsky et al, 2000), after which they were washed, and stored in distilled water at 4˚C until needed.…”
Section: Isolation Of Infective Eggsmentioning
confidence: 99%
“…AE were obtained by surgical remotion of the cuticle from adult worms 13 and LC was obtained from eggs eclosion 6 and larvae collection by Baerman Morales Method 16 . Erythrocyte superficial charge was studied by working with non -treated human erythrocytes (controls) and treated (T) ones, both washed in phosphate buffer saline (PBS) and resuspended to a 75% hematocrit.…”
mentioning
confidence: 99%